Renewable energy financing schemes for Indonesia. (Metro Manila, Philippines Asian Development Bank, 2019)
Despite recent efforts by the Government of Indonesia to promote renewable energy investments, fossil fuels continue to account for around 90% of the national power generation mix. High financing costs and low power purchase agreement tariffs have been identified as major roadblocks for renewable energy investments in the country. This report examines how an Energy Resilience Fund can be designed to overcome the investment challenges by providing financial incentives for renewable energy developers. It makes recommendations for the funds scope, structure, institutional design, function, and operation. Potential funding sources are also assessed.
Keywords: Renewable energy sources -- Indonesia; Industrial organization (Economic theory) -- Indonesia; Electronic books